Therapeutic faecal microbiota transplantation: current status and future developments - Borody, Thomas J. (Lippincott Williams & Wilkins, 2014)
PURPOSE OF REVIEW: Faecal microbiota transplantation (FMT) has undergone dramatic progression over the past year and continues to evolve as knowledge of the gastrointestinal microbiota (GiMb) develops. This review summarizes therapeutic advances in FMT, latest FMT therapies and presents the potential of FMT therapeutics in other gastrointestinal and extra-intestinal conditions. RECENT FINDINGS: The GiMb is now known to have a central role in the pathogenesis of many diseases. The success of FMT in curing Clostridium difficile infection (CDI) is well established and preliminary findings in other gastrointestinal conditions are promising. Published data from over 500 CDI cases suggest that FMT is generally well tolerated with minimal side effects. The commercial potential of FMT is being explored with several products under development, including frozen GiMb extract, which has been shown highly effective in treating relapsing CDI. Such products will likely become more available in coming years and revolutionize the availability and method of delivery of GiMb. SUMMARY: Recent literature unequivocally supports the use of FMT in treating relapsing CDI. Trials are underway to determine the therapeutic potential of FMT in other conditions, particularly inflammatory bowel disease. Therapeutic FMT is a dynamic field with new and emerging indications along with ongoing developments in optimal mode of administration.